2014
DOI: 10.4304/jltr.5.1.37-45
|View full text |Cite
|
Sign up to set email alerts
|

Pre-service English Teachers’ Vocabulary Learning Strategy Use and Vocabulary Size: A Cross-sectional Evaluation

Abstract: Abstract-After years of neglect, vocabulary has now been accepted as crucial to be able to interact in the target language. However, it may also become a challenge for learners to master a sufficient amount of vocabulary. It is argued that the use of vocabulary learning strategies leads to effective vocabulary learning. Addressing this relationship, different studies have focused on probing the dynamics of vocabulary learning. In this sense, the current study attempts to examine this issue for EFL university s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 13 publications
0
9
1
2
Order By: Relevance
“…As was stated above, there are a few studies that have been carried out on the relation between vocabulary size and VLS use. Some of them did not find any particular VLS that specifically correlated with vocabulary size, while some others found that determination strategies correlated with vocabulary size (Tanyer and Öztürk, 2014). Another study found (Alemdari, 2010) a relation between cognitive, determination and social strategies and vocabulary size.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…As was stated above, there are a few studies that have been carried out on the relation between vocabulary size and VLS use. Some of them did not find any particular VLS that specifically correlated with vocabulary size, while some others found that determination strategies correlated with vocabulary size (Tanyer and Öztürk, 2014). Another study found (Alemdari, 2010) a relation between cognitive, determination and social strategies and vocabulary size.…”
Section: Resultsmentioning
confidence: 98%
“…Quite recently, Tanyer and Öztürk (2014) carried out a study that focused on pre-service teachers' vocabulary learning strategy use and vocabulary size. Their study found that the most frequently used strategies were determination strategies despite the fact that it was not influential on pre-service teachers' vocabulary stock.…”
Section: Research On Vocabulary Learning Strategiesmentioning
confidence: 99%
“…2009 Komol ve Sripetpun, 2011;Lee, 2007;Memiş, 2018;Munandar, vd. 2015;Nacera, 2010;Nagy, 1997;Nation, 1990Nation, , 2001Oxford, 1990;Porte, 1988;Schmitt, 1997Schmitt, , 2007Syed, 2014;Şener, 2003, 2015Tanyer ve Öztürk, 2014;Tok ve Yığın, 2014;Waldvogel, 2013) genellikle kelime hazinesini geliştirme sürecinin öğrenci boyutuna odaklanmış ve tanımlanan stratejiler ile geliştirilen ölçekler de öğrencilerin kullandıkları/kullanabilecekleri stratejilere yönelik olarak ortaya koyulmuştur. Kelime hazinesini geliştirme süreci ve etkinlikleri düşünüldüğünde bu sürecin yalnızca dil öğrenenler tarafından yürütülmediği, aksine öğreticilerin de bu sürecin önemli ve ayrılmaz bir parçası olduğu söylenebilir.…”
Section: Alan Yazının Taranmasıunclassified
“…Çünkü kelime öğretimi uygulamaları, dil öğretim sürecine ayrılan sınırlı süre, bu süre içerisine sığdırılabilecek kelime sayısı, belli bir zaman diliminde zihnin öğrenilebileceği kelime kapasitesi ve hepsinden önemlisi öğrenmenin tamamıyla bireyin içsel bir süreci olması, yabancı dilde kelime öğretim çalışmalarının yanı sıra bireyin derste ve ders dışında kendi kelime öğrenimini düzenlemesini mümkün kılan stratejileri kullanmasını zorunlu hale getirmektedir . Kelime öğrenme stratejilerinin yabancı dil öğrenimi sırasında kullanımının bu sürece ve kelime hazinesinin gelişimine önemli katkıları olduğu yapılan birçok araştırmada ortaya çıkarılmıştır (Barcroft, 2009;Bozgeyik, 2011;Chang, 2014;Gu, 1994;Gu and Johnson, 1996;Hamzah, Kafipour, Abdullah, 2009;Lee, 2007;Nirattisai ve Chiramanee, 2014;Şener, 2003;Tanyer ve Öztürk, 2014;Waldvogel, 2013). Bu nedenle Türkçeyi yabancı/ikinci dil olarak öğrenenlerin kelime öğrenme stratejileri konusunda mutlaka daha fazla yönlendirilmeleri gerekmektedir.…”
Section: Tartışma Sonuç Ve öNerilerunclassified